The Ethical Concept of the Hadith Eating Procedures - Talisa Ilmalia; Sholihin Sholihin (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the ethical concept of eating procedures according to the hadith. This research is a qualitative type by applying literature study with the syarah method and using the maudhu'i approach. The results and discussion of this research include the term ethics, hadith about eating procedures, and an explanation of the ethics of eating procedures according to the hadith. This research concludes that some of the verses of the al-quran and the hadiths of the Prophet convey that Islam must have the concept of excellent health to do good deeds maximally which will lead to the success of the world and the hereafter. This research is expected to have beneficial implications as a treasure trove of knowledge for Muslims. This study recommends especially for Islamic religious extension workers to be able to provide understanding to Muslims about the ethics of eating according to the hadith. This study aims to discuss the ethical concept of eating procedures according to the hadith. This research is a qualitative type by applying literature study with the syarah method and using the maudhu'i approach. The results and discussion of this research include the term ethics, hadith about eating procedures, and an explanation of the ethics of eating procedures according to the hadith. This research concludes that some of the verses of the al-quran and the hadiths of the Prophet convey that Islam must have the concept of excellent health to do good deeds maximally which will lead to the success of the world and the hereafter. This research is expected to have beneficial implications as a treasure trove of knowledge for Muslims. This study recommends especially for Islamic religious extension workers to be able to provide understanding to Muslims about the ethics of eating according to the hadith.